The Influence Of Friendship On Character Formation: A Thematic Study Of Hadith From A Dramaturgical Perspective - Ritanti, Renata Anindhitya; Marhumah, Qoidatul; Masuwd, Mowafg Abrahem (LPPM UIN Syekh Wasil Kediri, 2025)
In the creation of a perfect human being, humans are unable to live alone without the presence of others. Seeing the reality, humans do need interaction between one another. From these interactions, some are mutually beneficial and some are detrimental. However, building a relationship, one of which is friendship, is not an easy thing. Because, everyone has their own nature and character. In real life, there are indeed detrimental friendship relationships, which only benefit one party and harm the other party. Therefore, this article was written to examine several issues related to the influence of friendship, to be used as an answer and understanding of existing problems. This article uses a qualitative method with a library research pattern or thematic hadith study literature research. The use of primary sources in this study is the hadith about friendship sourced from canonical hadith books, such as the books of Sahih Bukhari, Muslim, and others. While the secondary sources are narratives or articles related to the theme of the study. The study includes an analysis of the quality and quantity of hadith about friendship through takhrij and i’tibar sanad. Then how is the dramaturgy theory by Erving Goffman, and how is the interpretation of hadith with the perspective of the dramaturgy theory. The results of the study show that friendship has a significant influence on the formation of a person's character. Social interaction of friendship can shape social behavior positively or negatively. The hadith used is the hadith of Imam Bukhari about the importance of choosing friends. The analysis of the sanad of this hadith is declared to be valid in quality, because the sanad of the hadith is continuous, the narrator is 'fair and dabit. Furthermore, regarding the matan hadith, no irregularities or defects were found, nor do they contradict the verses of the Qur'an, authentic hadiths, historical facts, and scientific truths.